PERENCANAAN SISTEM PENYALURAN DAN PENGOLAHAN AIR LIMBAH DOMESTIK PADA PERUMAHAN PLAJAU INDAH DESA BAROKAH KABUPATEN TANAH BUMBU - Mahmud; Novia Astri Hasdita; Riza Miftahul Khair; Gusti Ihda Mazaya; Chairul Abdi (Prodi Teknik Lingkungan Fakultas Teknik Universitas Lambung Mangkurat, 2025)
Domestic wastewater in Plajau Indah Housing has not been appropriately managed. The gray water is discharged directly into the drainage without processing, and the black water is managed through septic tanks that are not up to standard. Further treatment is required after passing through the septic tank unit so that the effluent discharged does not contaminate groundwater. This final project aims to plan a domestic wastewater distribution and treatment system at Plajau Indah Housing with effluent quality referring to the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia number 68 of 2016 concerning domestic wastewater quality standards. This planning method includes licensing, literature study, primary data collection from direct field surveys, secondary data collection from relevant agencies, planning domestic wastewater distribution and treatment systems, designing domestic wastewater distribution and treatment units, and analyzing data results. The domestic wastewater distribution system uses a shallow sewerage system with centralized WWTP management (off-site) divided into 19 service blocks. The pipe diameters used in this design are 100 mm, 150 mm, and 200 mm. The average wastewater discharge in Plajau Indah Housing is 203.94 m3/day. The WWTP plans to use an aerobic-anaerobic combination, namely the Anaerobic Baffled Reactor with 5 compartments, 1 settling basin, and a modified trickling filter. The dimensions of the whole ABR tub are 30 m x 8 m x 2 m; the dimensions of the trickling filter from the results obtained are 3 m x 8 m x 2 m.